2018
DOI: 10.1080/0142159x.2018.1508829
|View full text |Cite
|
Sign up to set email alerts
|

A Best Evidence Medical Education (BEME) systematic review of: What works best for health professions students using mobile (hand-held) devices for educational support on clinical placements? BEME Guide No. 52

Abstract: Linkman (2019) A Best Evidence Medical Education (BEME) systematic review of: What works best for health professions students using mobile (hand-held) devices for educational support on clinical placements?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 76 publications
(127 reference statements)
0
46
1
7
Order By: Relevance
“…Systematic reviews in medical education require more open discussion of difficulties in synthesizing suboptimal evidence-bases and more systematic reporting of process analysis. In the example explored here, Maxwell dimensions [22,23] helped to classify and synthesize the variegated quantitative, qualitative, and mixed methods evidence-base of a systematic review [17] meaningfully and moderately reliably, when only one-third of articles reported 'quantitative-only' research. The dimensions also helped to illuminate a coherent relationship with K-levels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Systematic reviews in medical education require more open discussion of difficulties in synthesizing suboptimal evidence-bases and more systematic reporting of process analysis. In the example explored here, Maxwell dimensions [22,23] helped to classify and synthesize the variegated quantitative, qualitative, and mixed methods evidence-base of a systematic review [17] meaningfully and moderately reliably, when only one-third of articles reported 'quantitative-only' research. The dimensions also helped to illuminate a coherent relationship with K-levels.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [17]: What works best for health professions students using mobile (hand-held) devices for educational support on clinical placements? Evidence from n = 45 studies [35] plus giving a deliberative framework for reviewers to share understanding in a tricky integrative synthesis and consider possible gaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations